A rare case of human taeniasis caused by Taenia saginata with species undetermined cysticercosis. Issue 3 (19th March 2023) - Hou, Jie; Chen, Weilin; Chen, Rong; He, Chunlei; Ma, Ying; Qu, Junyan
Abstract: Abstract: Taeniasis and cysticercosis, which are caused by Taenia saginata, Taenia solium and Taenia asiatica, are zoonotic parasitic infections with a significant disease burden worldwide. There is consensus amongst experts that T. saginata is a common tapeworm that causes taeniasis in humans as opposed to cysticercosis. This case study of a middle-aged Tibetan man conducted in 2021 challenges the prevailing notion that T. saginata exclusively causes taeniasis and not cysticercosis by documenting symptoms and laboratory studies related to both taeniasis and multiple cysticercosis. The patient's medical record with the symptoms of taeniasis and cysticercosis was reviewed, and the tapeworm's proglottids and cyst were identified from the patient by morphological evaluation, DNA amplification and sequencing. The patient frequently experienced severe headaches and vomiting. Both routine blood screenings and testing for antibodies against the most common parasites were normal. After anthelmintic treatment, an adult tapeworm was found in feces, and medical imaging examinations suggested multiple focal nodules in the brain and muscles of the patient. The morphological and molecular diagnosis of the proglottids revealed the Cestoda was T. saginata. Despite the challenges presented by the cyst's morphology, the molecular analysis suggested that it was most likely T. saginata . This case study suggests that T. saginata infection in humans has the potential to cause human cysticercosis. However, such a conclusion needs to be vetted by accurate genome-wide analysis in patients with T. saginata taeniasis associated with cysts. Such studies shall provide new insights into the pathogenicity of T. saginata .